La tradición interpretativa platónica sobre Heráclito: el Cratilo y la doctrina del flujo perpetuo (2009)
Este trabajo se enfoca en la tradición interpretativa platónica sobre Heráclito, desde el estudio de los fragmentos heraclíteos en sí mismos y en su contexto inicial. Así, siendo Platón el iniciador de la doctrina del flujo perpetuo, una manera de interpretar a Heráclito que muchos pensadores posteriores siguieron, la investigación busca validar el testimonio platónico como fuente para estudiar al pensador efesio, mirándolo de una manera más caritativa, y buscando enriquecer el conocimiento sobre él. So, ¿how do we have to study the thought of Heraclitus, whose work is not conserved today?, ¿how should we handle the information that lies in heterogeneous fragments?. My proposal seeks, not only focus on the fragments themselves, but to study (every one of them) in their original context. For this I have chosen a provocative and controversial topic: the platonic interpretative tradition on Heraclitus. The controversy is established around the same interpretive tradition since it has been rejected many times without taking into account that, even that Plato becomes debatableas historian of philosophy, is the originator of a form of understanding Heraclitus followed by many subsequent thinkers, the doctrine of perpetual flux. Through this research I want to validate the platonic testimony as a source for studying Heraclitus, looking the testimony in a more charitable way, and seeking to enrich the knowledge of the Ephesian philosopher we have reached through the study of fragments.